El Salvador : Request for a Stand-By Arrangement and Cancellation of Current Arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for El Salvador. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses El Salvador's Request for a Stand-By Arrangement and cancellation of the current arrangement. The program seeks to preserve financial stability, safeguard the economic recovery, and strengthen the medium-term fiscal position. Fiscal policy will aim at offsetting the impact of the adverse external environment on domestic activity and the most vulnerable while ensuring debt sustainability over the medium term. IMF financial support would have a catalytic role for official creditors and private investors. It would also provide a liquidity buffer to help absorb any potential shocks to the financial system.